Implikasi Hukum Ekonomi Syariah dan Fiqh Muamalah Terhadap Operasional Lembaga Keuangan dan Bisnis Kontemporer - Jelita; Yusrina Nur Hidayah; Andini Id; Rahman; Mustatho (STIT Syekh Muhammad Nafis Tabalong, 2024)
This research discusses the implications of Sharia economic law and muamalah fiqh on the operations of contemporary financial and business institutions. Through a literature study, this research analyzes how the principles of Sharia economic law and muamalah fiqh influence operational strategies, financial performance, reputation and sustainability of financial institutions and businesses in facing increasingly complex global market dynamics. The research results show that the implementation of these principles has a positive impact on compliance with Islamic values, increasing public trust, stable long-term profits, and building a strong foundation for sustainable growth.